Barbara Queally : a 180 ? change in leadership style part a - Foote, Alison; Gaylard, Alison (London : Wits Business School, 2018)
The case explains how Barbara Queally founder and CEO of Garden Morris Packaging & Food came to do a leadership course at the University of Witwatersrand. The leadership course made Barbara realise that her leadership style was too authoritarian and she rarely listened to any input from her subordinates.
Originally Published InFoote, A., & Gaylard, A. (2018). Barbara Queally: A 180 ? change in leadership style part A. WBS-2018-5. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Queally, Barbara; Garden Morris Packaging & Food; University of the Witwatersrand; Leadrship -- Study and teaching -- Case studies